Dunia Anak di Era Digital dan Tantangan Pembelajaran Visual di Sekolah Dasar - Ambros Leonangung Edu; Elisabeth Irma Novianti Davidi (JIMAD: Jurnal Ilmiah Mutiara Pendidikan, 2026)
The development of digital technology has transformed how elementary school children interact with information through the dominance of images, videos, and interactive media, while instructional practices remain largely text-based and verbal. The mismatch between children’s neurocognitive characteristics and text-based instructional design creates a pedagogical gap that may hinder memory retention, attention, and learning motivation. This study aims to analyze the urgency of visual-based learning and the impact of textual design incompatibility on student learning outcomes in the digital era. The study employs a systematic literature review approach by synthesizing findings from neuroscience, cognitive psychology, and multimedia learning theory relevant to elementary education. The results indicate that the visual system has a strong neurobiological foundation, supports faster information processing, enhances long-term retention, and strengthens the formation of conceptual mental models when integrated with verbal narration. The findings also reveal that digitalization without instructional design grounded in cognitive principles risks generating excessive cognitive load and the screen inferiority effect. The study concludes that adaptive visual integration based on multimedia principles and cognitive load management constitutes a fundamental strategy for improving the quality of elementary education. The novelty of this research lies in its integrative neuro-pedagogical approach, which systematically connects neuroscience findings, learning theories, and instructional design practices to reconstruct the paradigm of twenty-first-century learning.